The Forms of the Coptic 2nd Person Feminine Singular Pronouns - Uljas, Sami (Zeitschrift für ägyptische Sprache und Altertumskunde, 2009)
The present article proposes a new analysis of the form and etymology of the Coptic 2nd person feminine singular suffix and prefix pronouns. It is suggested that in the tripartite conjugation and the conversions of the bipartite conjugation, the said person was expressed by using the bare pre-nominal conjugation base/converter (if such existed separately from the pre-pronominal form). Later, the bases and converters ending with re were reanalysed as consisting of a base + a suffix pronoun re. The rise of this new pronoun can be traced by studying manuscripts covering several centuries of language development. It is also proposed that the creation of the suffix motivated an analogous extension of re into the prefix of the 1 st present and future, where the older form te gradually gave way to a new and clearly secondary form ter.